Interprofessional collaboration among health professionals in cleft lip and palate treatment and care in the public health sector of South Africa - Phumzile Hlongwa; Laetitia C. Rispel (BMC, 2021)
Abstract Background Collaboration among different categories of health professionals is essential for quality patient care, especially for individuals with cleft lip and palate (CLP). This study examined interprofessional collaboration (IPC) among health professionals in all CLP specialised centres in South Africa's public health sector. Methods During 2017, a survey was conducted among health professionals at all the specialised CLP centres in South Africa's public health sector. Following informed consent, each member of the CLP team completed a self-administered questionnaire on IPC, using the Interprofessional Competency Framework Self-Assessment Tool. The IPC questionnaire consists of seven domains with 51 items: care expertise (8 items); shared power (4 items); collaborative leadership (10 items); shared decision-making (2 items); optimising professional role and scope (10 items); effective group function (9 items); and competent communication (8 items). STATA®13 was used to analyse the data. Descriptive analysis of participants and overall mean scores were computed for each domain and analysed using ANOVA. All statistical tests were conducted at 5% significance level. Results We obtained an 87% response rate, and 52 participants completed the questionnaire. The majority of participants were female 52% (n = 27); with a mean age of 41.9 years (range 22-72). Plastic surgeons accounted for 38.5% of all study participants, followed by speech therapists (23.1%), and professional nurses (9.6%). The lowest mean score of 2.55 was obtained for effective group function (SD + -0.50), and the highest mean score of 2.92 for care expertise (SD + -0.37). Explanatory factor analysis showed that gender did not influence IPC, but category of health professional predicted scores on the five categories of shared power (p = 0.01), collaborative leadership (p = 0.04), optimising professional role and scope (p = 0.03), effective group function (p = 0.01) and effective communication (p = 0.04). Conclusion The seven IPC categories could be used as a guide to develop specific strategies to enhance IPC among CLP teams. Institutional support and leadership combined with patient-centred, continuing professional development in multi-disciplinary meetings will also enrich IPC.